Quantum phase transitions probed by EPR spectra in dimeric spin arrays with supramolecular couplings - Calvo, Rafael (2023)
Dimeric compounds with nearly isolated molecular units (d-units) having pairs of spins s1 and s2 coupled by antiferromagnetic (AFM) exchange H0=-J0s1·s2 are non-trivial quantum spin systems having primary roles in magnetism. Weakly coupled infinite arrays of AFM d-units in crystal structures have an appealing spin dynamic arising from their energy-gapped level structure and display magnetic properties with important roles in materials science. They received great additional attention when it was discovered that the spin entanglement introduced by interdimeric couplings with magnitude J1 (with J1≪|J0|) gives rise to bosonic systems with novel properties and quantum phase transitions at high temperature (T). In this work, we collect recent advances in the interpretation of EPR spectral changes in terms of quantum phase transitions of arrays of d-units in the presence of weak interdimeric couplings. We review previous investigations of the problem and focused new experiments on the paradigmatic compound copper acetate monohydrate (CAH), collecting a detailed set of spectra in single-crystal and powder samples. The spectral features arising from this coupling are merging and narrowing of the peaks of the spectra of single crystals for specific magnetic field (B0) orientations, and an extraordinary “U-peak” in the powder samples associated with the quantum phase transition of the dimeric spin array. Our historical overview collects studies of similar compounds with the same dimeric feature in which the U-peaks were generally misinterpreted as a double-quantum transition, or ignored. We describe procedures to identify and quantify the U-peak and the merging and narrowing phenomena, with a protocol to extract the interdimeric coupling magnitude. As a novel contribution, we explain the experimental results by proposing a spin model with a microscopic flip-flop mechanism involving the absorption and emission of two simultaneous spin-one excitations having energy |J0|, connecting singlet and triplet levels of neighbor d-units and giving rise to a quantum phase displaying spin entanglement. This phase is tuned with the orientation of B0 applied along directions within “magic rings”, the positions where the EPR peaks of the dimeric units intersect, that we propose as a phase diagram. Our model considers explicitly the role of energy conservation in the process and allows analyzing and simulating the features of the EPR spectra arising from the couplings, describing their roles in the spectral behavior and the magnetic phases. In conclusion, we review the history of dimeric compounds and the possibility of detecting interdimeric couplings in the EPR spectra experimentally, and we introduce a novel spin model for the dimeric array appropriate to analyze EPR data which allows us to understand the spin dynamics and the phase transitions arising from these couplings.